Direct Oral Anticoagulants in Cancer Patients - Suryanarayan, Deepa; Lee, Agnes Y Y; Wu, Cynthia (Seminars in Thrombosis and Hemostasis, 2019)
Cancer-associated thrombosis (CAT) is a common occurrence in the journey of a cancer patient and its management poses significant challenges. Low molecular weight heparin (LMWH) is the standard of care but the high cost and the inconvenience of daily injections have led to low persistence with therapy. Direct oral anticoagulants (DOACs) are effective and safe for the treatment of venous thromboembolism (VTE) compared with vitamin K antagonist (VKA) therapy in noncancer patients, and emerging data comparing their use with LMWH in CAT are rapidly changing clinical practice. Recent randomized controlled trials also reported that specific DOACs are effective for primary prevention of CAT in patients undergoing systemic cancer therapy, but this benefit might be offset by an increased risk of bleeding. Undoubtedly, the option of an effective and safe oral anticoagulant is appealing to physicians and patients but critical limitations of DOACs, particularly bleeding and drug-drug interaction, need careful consideration. Understanding the scientific data, as well as each patient's preferences and values, are paramount in individualizing therapy in this special population of patients. This review summarizes the current evidence for DOACs for the treatment and prevention of CAT, discusses the importance of careful patient selection, and highlights upcoming new studies that will inform guideline recommendations.
Keywords: venous thromboembolism; cancer associated thrombosis; direct oral anticoagulants; low molecular weight heparin